Keterlibatan Md. Juhdi Ma’mur Dalam Organisasi Pembela Tanah Air (Peta) Di Banten Tahun 1943-1945 - milasari handayani; zaenal abidin; Eva Syarifah Wardah (Departement of History and Islamic Civilization, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2018)
Muhamad Juhdi Ma’mur is one of the leaders of the Banten fighters who came from the village of Pancaregang, Pancanegara, Pabuaran district. Juhdi born in year 1917 and died in the year 1945. Juhdi Ma’mur is an Indonesian Defense Defender (PETA) who served as the Platoon Commander and become a member of the People’s Security Agency. On October 3, 1943 was established PETA which serves to maintain the homeland. PETA the first time is was established in Banten was Daidan I under the leadership of K.H Syam’un and Daidan II under the leadership of the leadership E.O Ternaya. In the beginning Daidan I domiciled in Serang then moved to Labuan. K.H Syam’un founded Daidan III in Cilegon again. Daidan I in Labuan was handed over to K.H Khatib, next set up Daidan IV led by Tb. Uding Suryatmaja.